Our eight years experience in postintubation/posttracheostomy tracheal stenosis - Ozgul, Mehmet Akif; Gul, Sole; Cetinkaya, Erdogan; Turan, Demet; Kirkil, Gamze; Ugur Chousein, Efsun Gonca; Ozgul, Guler (Turkish Assoc Tuberculosis & Thorax, 2019)
Introduction: The most common cause of tracheal stenosis (TS) continues to be traumas according to the intubation and tracheostomy. Bronchoscopy is considered the gold standard for the detection and diagnosis of tracheobronchial pathology. There are several treatment options. We aimed to discuss our tracheal stenosis patients' treatment options, and their follow-up period. Materials and Methods: Consecutive referred patients between 2009 and 2018 presenting with TS were reviewed for the study. Demographic characteristics, localization, length and degree of stenosis, treatment techniques, postoperative complications, and survival were recorded for all patients. Results: A total of 110 patients included. The mean age was 53.7 +/- 16.7 (1698 years) years. Of 110 patients, 54 (49.1%) were female. Most common type of stenosis was complex stenosis (74.5%). Mechanical dilatation was applied to all patients. Stenotic regions of 22 (20%) patients were cut with bronchoscopic scissor. Tracheal stents were inserted into trachea of 49 (44.5%) patients. During follow-up period; 36 of 110 (32.7%) patients had surgical resection. Six of 36 (16.7%) patients died during follow-up period (one of them died during surgery), 17 (47.2%) patients had total recovery after surgery. Thirteen of 36 (36.1%) patients had restenosis after surgery. Conclusion: Tracheal stenosis is a process seen after postintubation or posttracheostomy frequently and it has a wide range of management modalities. Although, it is believed that surgery is the most efficient technique in cases without medical contraindications, we determined that endoscopic interventions can be alternative therapeutic options for inoperable patients. Patients must be followed-up after interventional therapies because complications, and restenosis can usually be seen.
Postentübasyon/posttrakeostomi trakeal stenozlarda 8 yıllık tecrübemiz
Keywords: Postintubation tracheal stenosis; posttracheostomy tracheal stenosis; treatment